A posteriori error estimation techniques for non-linear elliptic and parabolic pdes - Verfiirth, Rudiger (European Journal of Computational Mechanics, 2000)
We give a brief overview of a posteriori error estimation techniques for nonlinear elliptic and parabolic pdes and point out some related questions which are not yet satisfactorily settled.